Disain Peredam Suara Berbahan Dasar Sabut Kelapa dan Pengukuran Koefisien Penyerapan Bunyinya - Khuriati, Ainie; Komaruddin, Eko; Nur, Muhammad (BERKALA FISIKA, 2006)
research aims to determine sound absorption of absorber materials making from coconut coir composites. Absorber material have been made with different composition from coconut coir composites. Twelve samples have been made. One of samples is natural coconut coir and the other are made from coco fiber and coco peat with certain compositions. From 12 samples, 10 samples have been tested. Absorption coefficients was measured by impedance tube method with ASTM E-1050:1990 standardization. The experiment results show that coconut coir is up to standard for absorber material according to ISO 11654 , that is with weigthed absorption (aw) over 0,15. Weigthed absorption of samples are, A:0,30; B:0,44;C:0,27;D:0,44; E:0,51; F:0,44; G :0,47; H:0,49; I:0,31;J:0,41. So samples A,B,D,E,F,G,H,I and J can be classified in class-D while sample C in class-E. Absorber materials that have been made are also compatible with marketed products. The best composition for absorber was mixture of coco dust and coco fiber. Improving amount of coco fiber improve maximum absorption. Adding air cavity between samples and wall improve absorption. Improving mass density of sample making with similar total mass of composition and similar glue improve absorption in low frequency. Keyword: coconut coir, coco fiber, coco peat, sound absorber, impedance tube, absorption coefficient, pore.